Cardiac computed tomography imaging in familial hypercholesterolaemia: implications for therapy and clinical trials. Issue 6 (December 2015) - Sijbrands, Eric J.G.; Nieman, Koen; Budoff, Matthew J.
Abstract : Purpose of review: The purpose of the present review is to summarize the potential clinical applications of computed tomographic angiography (CTA) in familial hypercholesterolemia so far and recent advances of CTA research in other high-risk patients. Recent findings: Long-term, aggressively statin-treated, asymptomatic familial hypercholesterolemia patients may still have dramatic coronary artery disease (CAD). A clear association between the presence and the extent of nonobstructive CAD and all-cause mortality was found in the COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter registry. Notably, baseline statin therapy was associated with a significantly lower mortality for individuals with atherosclerotic plaque on CTA, but not for individuals with normal coronary arteries. Summary: CTA imaging has made clear that an increased plaque burden can be present even among asymptomatic, long-term aggressively statin-treated familial hypercholesterolemia patients. In the COronary CT Angiography EvaluatioN For Clinical Outcomes: An InteRnational Multicenter registry, nonobstructive CAD predicted all-cause mortality and statin treatment improved the life span of persons with nonobstructive CAD. Clinical trials with CTA are required to develop and test identification of CAD and personalized treatment strategies for familial hypercholesterolemia.